Enhancement of planar Hall sensitivity with the assistance of a CuIr spin-orbit torque biasing layer - Demirci, Erdem; Ozturk, Mustafa (Springer Heidelberg, 2023)
To enhance the operating performance of the PHE sensor in this study, we focused on the sensitivity of exchanged biased Py/CuIr (t(CuIr))/IrMn ultra-thin films. CuIr was chosen as a spacer layer, which is known to exhibit the large spin Hall angle required to obtain the spin-orbit torque biasing field. Herein, CuIr spacer layer thickness was varied from 0 to 20 angstrom and a dramatic enhancement in the field sensitivity up to 20 angstrom was observed. This enhancement was explained by the correlation between exchange bias and SOT biasing field.
Keywords: Magnetic sensors; Planar Hall effect; Spin Hall angle; Spin-orbit torque; Exchange bias; CuIr; Spacer layer